Horichia Jenny - Pupulin, Franco (2022)
Rarity, in orchids, is often closer to a perception than to a specific category of frequency, assessed on the basis of documented data. Rare species are frequently only a way to say that they are rarely seen in living collections or museums, and this scarcity is assumed as a reflection of true rarity in nature as well. So “rarely seen” orchids are not necessarily rare in the field, but simply small and difficult to spot; completely “non-ornamental” and neglected to the point of becoming almost invisible; or plants that are difficult to collect or cultivate. We discussed the topic a few years ago, when recording the presence of Horichia dressleri Jenny in Costa Rica for the first time